Uncovering Barriers to Prenatal Physical Activity and Exercise Among South African Pregnant Women: A Cross-Sectional, Mixed-Method Analysis - Okafor, Uchenna Benedine; Goon, Daniel Ter (Frontiers in Public Health, 2022)
Background The barriers to prenatal physical activity and exercise have been widely reported in the literature, highlighting context-specific challenges. However, generally, research on prenatal physical activity and exercise among pregnant women in South Africa is rare; and particularly concerning the barriers to their prenatal physical activity practice. This study assessed the barriers to physical activity participation among pregnant women in the Eastern Cape, South Africa. Methods This was a sequential explanatory mixed method, predominantly quantitative study involving 1,082 pregnant women. A structured self-administered questionnaire on perceived barriers to physical participation was applied to collect quantitative data; while a subset of 15 pregnant women participated in individual in-depth semi-structured interviews to augment quantitative data. Quantitative and qualitative data were analyzed using descriptive statistics and thematic analysis, respectively. Results The results of the quantitative analysis presented major barriers: lack of advice on prenatal physical activity and inadequate or conflicting information about prenatal physical activity; tiredness; work commitments; discomfort; lack of time; low energy; non-accessibility to physical activity; lack of financial resources, and safety concerns for the mother and the baby. Qualitatively, the barriers identified relate to four main themes: individual, lack of information, lack of resources, and environmental barriers. Conclusion The major barriers cited by the women were tiredness, lack of time, discomfort, and low energy. They also include lack of support, advice and information about prenatal physical activity. The multiple constraining factors responsible for low or non-prenatal physical activity of pregnant women in this setting highlight the need to tailor interventions to address their individual uniquely perceived barriers.